Inovasi Pelayanan Patriot Melalui Aplikasi Fishgo Sebagai Upaya Peningkatan Kesejahteraan Nelayan Di Kabupaten Badung - Ida Ayu Kumara Devi; Putu Nomy Yasintha; I Putu Dharmanu Yudharta (Jurnal Akuntan Publik, 2023)
The FishGo application is a navigation-based android application using remote sensing sensor technology that is processed with a certain algorithm so that it can provide information on potential fish areas and the best route for traditional fishermen to catch fish. The Patriot Tool (Detecting Fish Catching Areas Using the Internet of Things System) is a development of an application in the form of a fish finder tool to more accurately detect underwater fish biomass. The research objective is to determine the success of patriot service innovation through the FishGo application as an effort to improve the welfare of fishermen in Badung Regency. The research method is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The research analysis uses the theory of innovation success factors put forward by Bugge, et al which consists of 6 indicators: Governance and innovation, Sources of ideas for innovation, Innovation culture, Capabilities and tools, Objective, outcomes, drivers and trouble, and Collecting innovation data for single innovation. The results of this study are that the implementation of innovation has achieved good results on the source of innovation ideas including internal and external, a culture of innovation by showing good changes to fishermen, cooperation in developing innovation and socialization activities that are intensively carried out to fishermen, the results felt by fishermen experience catch increase. However, innovation governance is still not optimal, there are no basic regulations such as regional regulations and SOPs governing innovation, Human Resources capabilities still need to be added to the fields of electronics, IT and mapping, goals that have not been fully achieved from those that have been set. and there are still external and internal obstacles in its implementation.